Antioxidant, physicochemical, and sensory properties of buffalo meat patties incorporated with roselle (Hibiscus sabdariffa L.), wolfberry (Lycium barbarum L.), and beetroot (Beta vulgaris L.) purées - Ismail, N. A.; Ab Aziz, M. F.; Ismail-Fitry, M. R. (UPM Press, 2022)
The present work evaluated the antioxidant, physicochemical, and sensory properties of buffalo meat patties incorporated with 2% roselle (Hibiscus sabdariffa L.), wolfberry (Lycium barbarum L.), or beetroot (Beta vulgaris L.), and chill-stored (4°C) for 11 days. 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, 2-thiobarbituric acid reactive substances (TBARS), shrinkage, cooking yield, water holding capacity, pH, colour, textural properties, and sensory evaluation of the patties were examined. Patties incorporated with roselle, wolfberry, and beetroot had increased scavenging activity, thus decreasing oxidative activity in the patties during storage. Cooking yield was improved in all treatments with significant decrease in pH in both cooked and uncooked roselleincorporated patties. No changes were observed for the texture of all samples, while roselle-incorporated patties maintained the redness after the 11th day of storage. Sensory attributes of the modified patties were acceptable to all panellists. In conclusion, the incorporation of roselle in buffalo meat patties showed more beneficial effects than the other purées tested in improving the quality of the patties while maintaining their sensory properties.